QOLP-19. A NEW MODEL OF CARE FOR PATIENTS WITH CENTRAL NERVOUS SYSTEM CANCERS. (11th November 2019) - Nevel, Kathryn; Konig, Franchesca; Elizabeth Davis, Mary; Skakodub, Anna; Sibilla, Maryann; Harrison, Mabel; Rawlins-Peters, Gayle; Jean-Charles, Dominique; Zankowsky, Anastasia; Gilman, Jody; Kelly, Brian; Reiner, Anne; et al.
Abstract: Patients (pts) with primary or metastatic central nervous system (CNS) cancers often have multiple physical, psychosocial, and spiritual needs. Neurological impairments can transform relationship dynamics with caregivers. These issues are difficult to address within a single outpatient oncology clinic. The Neurological Multidisciplinary Care Clinic (MdCC) at Memorial Sloan Kettering Cancer Center was a pilot study from 08/2017 to 04/2019 to foster a new model of care for complex pts with CNS cancers to identify and address their needs. The MdCC team: a neurologist, nurse, physiatrist (RM), physical therapist, social worker (SW), case manager (CM), dietitian (RD), and chaplain saw each pt/caregiver during a 3-hour visit. Since 11/2017 participants completed validated surveys on unmet needs, financial strain, and home equipment prior to their visit and satisfaction surveys afterward. Descriptive statistics were used to analyze results. Seventy-eight pts were seen: 39 were female, median age 59. Of these 78 pts, 65 had primary CNS cancers; predominantly glioblastoma (52%) and high-grade glioma (29%). Over 60% had never seen a SW, CM, RD, or physiatrist prior to MdCC. Seventy-six pts (97%) received symptom management recommendations. Prognosis/coping with cancer was discussed with 72 (92%) which increased signed health care proxy forms by 17% and DNR orders by 6% at time or within a month post MdCC. New/updated physical therapy was ordered for 48 pts (61%), orthotics for 8 (10%), and new equipment for 12 (15%). 25 pts (32%) continued following with physiatrists. Forty-eight pts completed a satisfaction survey; of these, 96% were highly satisfied, and would recommend MdCC to others. Pts'/caregivers' unmet needs were effectively identified and addressed in this new model, The presence of these providers at time of MdCC allows for real time assessment of pts'/caregivers', their support system, multidisciplinary team collaboration, planning, coordination of community services and implementation of a safe patient centered plan of care.